Analysis of Stability Improvements by Using Capacitors - ., Yusmartato; Pelawi, Zulfadli; ., Ramayulis; Krianto Sulaiman, Oris; Hasibuan, Abdurrozzaq; Asaad, Mhd.; Rahman Rambe, Muhammad; ., Usman; Napid, Suhardi (International Journal of Engineering and Technology, 2018)
The demand for electricity has increased substantially while the expansion of electricity generation, power transmission is very limited, due to environmental restrictions, consequently some transmission lines, limiting power factor. Power flow in the generation system, covering the area of North Sumatra and Aceh which is managed by PT. PLN (Persero), ETAP 4.0 (Electrical Transient Analizer Program) is a program that can display GUI (Graphical User Interface) with unlimited bus number, ETAP 4.0 is useful for Power flow study. The data required by ETAP 4.0 on a generation system is a one-line diagram, nominal kV, and generator, bus, transformer, transmission, and safety rating. The power flow approach method used is the Newton-Raphson method with maximum iteration of 99 and the accuracy of 0.000001. The problem of power flows under consideration is the normal state system, one transmission is disconnected, one of the plants is not operating. The results of the power flow study for each problem obtained the lowest bus voltage, the highest losses in the transmis. The largest power distributed in power plants, new in high voltage transmission, increases the power of power from power to load, changes in voltage problems and improves system stability. This paper aims to verify the capacitor’s ability to improve voltage regulation (voltage stability) in electric power transmission systems, from this capacitor simulated using ETAP 4.0 included in Newton-Raphson model.